Alterations in the lipid composition of pectoral muscles in honey bees (Apis mellifera) in relation to brood-rearing activity - Kovalskyi, I. V.; DruzhbiakМ. A.; Kovalska, L. M.; Druzhbiak, A. J.; Tybinka, A. M.; Klym, O. Y.; Boyko, A. O.; Zhmur, V. V.; Havdan, R. V.; Perig, D. P.; Lunyk, I. M.; Fiialovych, L. M.; et al. (Regulatory Mechanisms in Biosystems, 2026)
Colony preparation for hypobiosis is associated with the emergence of highly viable individuals. Autumn bees possess significantly greater longevity due to a physiological state defined by reduced metabolic activity. This preparatory process is evidenced by diminished brood rearing and decreased flight activity in response to natural factors. Consequently, young bees cease brood care and begin to accumulate increased quantities of proteins, lipids, and glycogen in the fat body. In this context, intensive brood rearing may be regarded as a stressor that significantly affects both energy metabolism and plastic processes within the insect organism. Research findings indicate that this factor determines both the total lipid content and the distribution of lipid classes in various tissues prior to the onset of hypobiosis, with particular reference to the thoracic flight muscles of bees. Given their principal role in thermogenesis, the structural organization of muscle tissue and its functional state substantially influence the metabolic activity and physiological condition of the insects, thereby affecting the overall success of colony overwintering. The pectoral musculature of honey bees constitutes a highly specialized, energy-demanding system whose activity is supported by the mobilization of reserves from the fat body. Accordingly, lipid accumulation within these muscles for winter survival does not take place. The lipids present are largely associated with mitochondria and serve as substrates for prompt oxidative metabolism, rather than as strategic reserves. Their proportion in muscle tissue is considerably lower than that of proteins and glycogen. Analysis revealed that the total lipid content in the pectoral muscles of worker bees ranged from 62.4 to 80.1 mg/g of tissue mass. The cessation of brood rearing in the experimental colonies led to significant quantitative and qualitative changes in muscle total lipid composition, affecting both total lipid levels and the relative distribution of lipid fractions. Specifically, total lipid content increased by 17.6% in the experimental group (P < 0.001). Additionally, the complete cessation of brood rearing resulted in a 2.75% increase in phospholipid content within the pectoral muscles (P < 0.001), a change that influences the functional stability of cellular membranes. The experimental group also exhibited a 4.6% reduction in free cholesterol levels, a key determinant of membrane fluidity. Furthermore, the 2.89% increase in triacylglycerol content observed in the experimental group suggests an adaptive response to low-temperature conditions. In general, the changes associated with the brood-rearing factor exert a detr i mental effect on the physiological status of autumn bees. As a consequence, these individuals acquire features typical of aged summer bees and demonstrate a shortened lifespan, thereby reducing their capacity to successfully endure the winter period. This ultimately compromises colony overwintering success, spring development, and productivity in the subsequent season.